Physical properties of root cementum: Part 11. Continuous vs intermittent controlled orthodontic forces on root resorption. A microcomputed-tomography study - Ballard, Darin J.; Jones, Allan S.; Petocz, Peter; Darendeliler, M. Ali (American journal of orthodontics and dentofacial orthopedics, 2009)
There is still ambiguity about whether continuous or intermittent orthodontic forces produce more root resorption. This prospective randomized clinical trial was designed to compare root resorption with these 2 force application patterns. The sample consisted of 16 maxillary first premolars from 8 patients who required bilateral extractions as part of their orthodontic treatment. In each subject, a fixed experimental appliance was placed on the maxillary teeth on each side, allowing a buccally directed force. The force was generated by a segmental wire of β-titanium-molybdenum alloy. The first premolar on 1 side received a buccally directed continuous force, and the contralateral premolar received intermittent force. The initial force magnitude for both sides was 225 cN. After 14 days of initial continuous force, the intermittent force application was obtained with subsequently repeated periods until the end of the eighth week of a 3-day rest period followed by a 4-day force application period. Force levels were set to 225 cN at each patient visit. After the experimental period of 8 weeks, the teeth were extracted under a strict protocol to prevent root surface damage and analyzed with a microcomputed-tomography scan system, and specially designed software was used for direct volumetric measurements. Intermittent force produced less root resorption than continuous force ( P <0.05). Analysis by position showed that the buccal-cervical region had significantly more root resorption than the other positions ( P <0.001), corresponding to a region of compression generated by tipping. The application of intermittent orthodontic forces of 225 cN for 8 weeks (14 days of force application, 3 days of rest, then 4 days of force application repeated for 6 weeks) caused less root resorption than continuous forces of 225 cN for 8 weeks. Although it might not be clinically practical, compared with continuous forces, intermittent forces might be a safer method to prevent significant root resorption. This regimen, however, could compromise the efficiency of tooth movement.